ASPEK PERJANJIAN KERJA WAKTU TERTENTU MENURUT KUHPERDATA DI INDONESIA - Irwan Jaya Zay; Suhendro Suhendro; Yetti Yetti (Borneo Law Review, 2021)
AbstractAn agreement is an event where one person without a loan or where two people promise each other to do something. The agreement issues an agreement between two people that is made. agreement in the form of a quote containing promises or promises that are spoken or written. The employment agreement is also contained in Article 1601 a BW, namely "a search agreement is an agreement with the name of one party, binding himself under the orders of another party, the employer, for a certain period of time, doing work by receiving wages, labor agreement giving birth employment relationship, between employers and workers based on work agreements, who have jobs, wages and orders. The work agreement which in Dutch is usually called Arbeidsovereenkoms, the first definition is stated in the provisions of Article 1601a of the Civil Code which states that: "A work agreement is an agreement in which the first party, the worker, binds under the leadership of another party, the employer, for a certain period of time, performs under the leadership of another party, the employer, for a certain time. wages. “There are relatively few violations or legal aspects committed by employers related to the provision of workers' rights. However, it is the opposite in the regions. Employers have the maximum time limit permitted by Law Number 13 of 2013 concerning the period of PKWT. The provision of workers' rights that are given time such as wages, working hours and social security still does not meet expectations. lies in two things, the first factor is the implementation of the PKWT rules that are not in accordance with the requirements. Employers should not hire workers for something that is not needed in the course of the company. Most of the types and nature of work required are jobs that are part of the core work of the production process and are permanent in nature. So that there has been a fatal violation of Article 59 of the Manpower Law, which is caused by the object of work that is prohibited by the provisions of the law against PKWT. Judging from the fact that the time allotted, workers should have changed their status to PKWTT, because they have been doing permanent work.Keywords: PKWT certain time work agreements, unlawful